Characterization of Laccase-Treated Kenaf Fibre Reinforced Recycled Polypropylene Composites - Beg, M. D. H.; M. R., Islam (North Carolina State University, 2013)
Raw and laccase-treated kenaf fibre (KF) were used individually to reinforce recycled polypropylene (RPP) using extrusion and injection moulding. Laccase was used to modify the surface of the fibre to improve the compatibility between fibre and matrix. Enzyme concentration and soaking time were considered as the treatment parameters. Maleic anhydride grafted polypropylene (MAPP) was used with a ratio of 1:10 as coupling agent to fibre. Fibres were characterized by density, energy dispersive X-ray (EDX), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), and scanning electron microscopy (SEM), whereas composites were characterized by density, melt flow index (MFI), mechanical tests (tensile, flexural, and impact), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), field emission electron microscopy (FE-SEM), and water uptake analysis. Density, O/C ratio, and crystallinity of the treated fibre were increased. An optimum fibre loading of 40% gave the highest tensile properties. Tensile strength improved due to coupling agent by 37%, whereas treatment of fibre did the same by 40%. Flexural, impact, and thermal properties of the composites and crystallinity of the matrix were improved due to treatment. Morphological images of the composites showed better adhesion, and moisture absorption was reduced by 37% due to treatment and use of coupling agent.